Effects of intermittent negative pressure and active recovery therapies in the post-match period in elite soccer players: A randomized, parallel arm, comparative study - Souto Maior, A.; Tannure, M.; Eiras, F.; de Sá Ferreira, A. (Biomedical Human Kinetics, 2020)
Study aim: This study compared the effects of intermittent negative pressure therapy (INPT) vs. active recovery therapy (ART) on post-match physiological parameters such as serum CK level and skin temperature of the lower limbs in elite soccer players.